Immune Deficiency Does Not Increase Inflatable Penile Prosthesis Reoperation Rates. Issue 8 (21st July 2021) - Gaffney, Christopher D.; Fainberg, Jonathan; Punjani, Nahid; Aboukhshaba, Ahmad; Pierce, Hudson; Patel, Neal; Zheng, Xinyan; Sun, Tianyi; Sedrakyan, Art; Kashanian, James A.
ABSTRACT: INTRODUCTION: Immunocompromised patients are postulated to have higher rates of post-operative infection. We sought to determine if inflatable penile prosthesis (IPP) reoperation rates (due to infection, erosion, device malfunction or patient dissatisfaction) are higher among immunocompromised men. Methods: We analyzed men who underwent initial IPP insertion from 2000 to 2016 in the New York Statewide Planning and Research Cooperative System database. Immunocompromised patients were propensity-score matched in a 1:3 fashion with immunocompetent patients. We estimated and compared reoperation rates (including removal, reoperation due to infection, revision, or replacement of an IPP after an index procedure) at 30 days, 90 days, 1 year and 3 years of follow up between immunocompromised men and controls by performing a Kaplan Meier analysis and Log-rank tests. Cox proportional hazards models were built to examine the overall association between immune deficient status and the risk of reoperation. Main Outcome Measure: Reoperation rate and time to reoperation after index IPP placement. RESULTS: A total of 245 immunocompromised patients who received an initial IPP between 2000 and 2016 were identified. After propensity score matching, we analyzed 235 immunocompromised men and 705 controls. There was no difference in overall reoperation rates between immunocompromised men and controls within any time period assessed (30 days, 90 days, 1 year, or 3 years). In our Cox proportional hazards model, the hazards of overall reoperation, removal, or revision/replacement (HR 1.11 [95% CI 0.74–1.67], HR 1.58 [95% CI 0.90–2.79)], and HR 0.83 [95% CI 0.47–1.45], respectively) were not significant different between immunocompromised men and controls. Reoperation due to infection was also not significantly different between immunocompromised and immunocompetent men (HR 2.06 [95% CI 0.97–4.40]). Strengths & Limitations: This study is strengthened by its size as the largest cohort of immunocompromised men treated with IPP to date in the literature, but is limited by the retrospective nature of the database which may introduce selection bias and by the low event rate for IPP reoperation. CONCLUSIONS: Reoperation rates, including those due to infection, are not significantly different between immunocompromised men and immunocompetent controls. Therefore, immune status in appropriately selected candidates does not appear to place patients at substantially higher risk of explant or revision.